RAGE supports parathyroid hormone-induced gains in femoral trabecular bone - Philip, Binu; Childress, Paul J.; Robling, Alexander G.; Heller, Aaron; Nawroth, Peter Paul; Bierhaus, Angelika; Bidwell, Joseph P. (American journal of physiology. Endocrinology and metabolism, 2010)
Parathyroid hormone (PTH) restores bone mass to the osteopenic skeleton, but significant questions remain as to the underlying mechanisms. The receptor for advanced glycation end products (RAGE) is a multiligand receptor of the immunoglobulin superfamily; however, recent studies indicate a role in bone physiology. We investigated the significance of RAGE to hormone-induced increases in bone by treating 10-wk-old female Rage-knockout (KO) and wild-type (WT) mice with human PTH-(1-34) at 30 μg·kg−1·day−1 or vehicle control, 7 days/wk, for 7 wk. PTH produced equivalent relative gains in bone mineral density (BMD) and bone mineral content (BMC) throughout the skeleton in both genotypes. PTH-mediated relative increases in cortical area of the midshaft femur were not compromised in the null mice. However, the hormone-induced gain in femoral cancellous bone was significantly attenuated in Rage-KO mice. The loss of RAGE impaired PTH-mediated increases in femoral cancellous bone volume, connectivity density, and trabecular number but did not impact increases in trabecular thickness or decreases in trabecular spacing. Disabling RAGE reduced femoral expression of bone formation genes, but their relative PTH-responsiveness was not impaired. Neutralizing RAGE did not attenuate vertebral cancellous bone response to hormone. Rage-null mice exhibited an attenuated accrual rate of bone mass, with the exception of the spine, and an enhanced accrual rate of fat mass. We conclude that RAGE is necessary for key aspects of the skeleton's response to anabolic PTH. Specifically, RAGE is required for hormone-mediated improvement of femoral trabecular architecture but not intrinsically necessary for increasing cortical thickness.
Zuerst veröffentlicht 22. Dezember 2009
Gesehen am 03.05.2023